Parental Educational Responsibility Beliefs, Parenting Efficacy Beliefs, and Adolescents' Academic Achievement in China: Evidence From CEPS - Xie, Yongxiang; Li, Yijiang (Psychology in the schools, 2025)
This study uses data from the China Education Panel Survey (CEPS) to examine how parental educational responsibility beliefs and parenting efficacy beliefs relate to adolescents' academic achievement. It also explores whether parental educational expectations mediate these relationships and how they vary by adolescents' level of conscientiousness. The study reveals that parental educational responsibility beliefs are negatively correlated with adolescent academic achievement, while parenting efficacy beliefs are positively correlated. Parental educational expectations partially mediate the relationships between parental educational responsibility beliefs, parenting efficacy beliefs, and academic achievement. Additionally, the association between parental educational responsibility beliefs and academic achievement is attenuated among adolescent with high levels of conscientiousness. These findings highlight the importance of positive parental educational responsibility beliefs and parenting efficacy beliefs in promoting children's academic achievement. Parental educational responsibility beliefs are negatively correlated with adolescent academic achievement, while parenting efficacy beliefs are positively correlated. Parental educational expectations partially mediate the relationships between parental educational responsibility beliefs, parenting efficacy beliefs, and academic achievement. The association between parental educational responsibility beliefs and academic achievement is weaker among adolescent with high levels of conscientiousness.